P557 Review of Incidence and indication of Micturating Cystourethrogram (MCUG) in paediatric patients in Cork University Hospital (CUH). (June 2019) - Stephens, Carol; Flanagan, Sean
Abstract : Micturating Cystourethrogram (MCUG) is commonly uses to investigate Vesocoureteroreflux (VUR). While the test lends itself to a high sensitivity and specificity rate in identification of VUR it doesn't come without risks. The biggest challenge is practicality and tolerability. MCUGs are not pleasant and the window of opportunity to perform them without sedation is narrow. Furthermore, MCUG is an invasive test predisposing the patient to iatrogenic infection. Keeping the above in mind, it is essential that MCUGs are only performed in those who need them and will influence their future management and treatment Aims: Identify all children in who had a MCUG at less than two years of age Identify the indication for MCUG Investigate if reason for MCUG met guidelines. Methods: A retrospective review of MCUGs performed in CUH in all children less than two years of ages between 01/01/15–31/12/17.Patients from Cork University Maternity Hospital were included.Patients were identified via IMPAX Radiology system. Nice Guidelines were used as the standard. Results: Ninety nine children were identified: Two children met more than one indication; atypical UTIs and hydronephrosis One child had more than three indications; hydronephrosis, scarring and 'other' The main reasonfor not meeting criteria was for recurrent UTIs outside the <6 month of age period. Discussion: MCUG is recommended in children who have had a renal ultrasound revealing hydronephrosis, scarring or other findings that may suggest high grade reflux or in children less than six months with atypical and or recurrent UTIs. There is considerable controversy regarding the optimal management of VUR varying between prophylactic antibiotics versus surgery. Early identification optimizes kidney preservation. By defining risk, early stratification allows earlier identification of high risk children .Incidence of VUR has been difficult to ascertain but it has been estimated that 0.8–1.4% of normal children will have reflux. This incidence soars to 30–50% in children with UTIs depending on age and a higher incidence in males despite a higher incidence of UTIs in females. In our hospital, we adhere to current best medical practice and don't perform MCUGs when not indicated. This is important given the significant risks associated with MCUGs. Conclusion: The majority of MCUGs were performed in line with current guidelines. The most common indication was hydronephrosis. There is good knowledge among paediatric and radiology teams of the best practice.